2019
DOI: 10.3390/en12020253
|View full text |Cite
|
Sign up to set email alerts
|

Strength Behaviors of Remolded Hydrate-Bearing Marine Sediments in Different Drilling Depths of the South China Sea

Abstract: The mechanical behaviors of hydrate-bearing marine sediments (HBMS) drilled from the seafloor need to be understood in order to safely exploit natural gas from marine hydrate reservoirs. In this study, hydrates were prepared using ice powder and CH4 gas, and HBMS from the Shenhu area in the South China Sea were remolded using a mixed sample preparation method. A series of triaxial tests were conducted on the remolded HBMS to investigate the effects of soil particle gradation and the existence of hydrate on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Table 1 provides details of a range of studies on HBS to determine its strength. This list is not exhaustive and excludes duplication of test results from the same authors, and tests conducted on predominantly fine-grained soils, such as that reported by Li et al (2012Li et al ( , 2019. The strength and stiffness of granular soils have been shown to be highly dependent on numerous factors related to soil properties (porosity [directly related to void ratio, density]), grain characteristics (particle size and shape), and test conditions (effective stress, strain rate).…”
Section: The Geomechanical Behavior Of Laboratory Synthesized Gas Hyd...mentioning
confidence: 99%
“…Table 1 provides details of a range of studies on HBS to determine its strength. This list is not exhaustive and excludes duplication of test results from the same authors, and tests conducted on predominantly fine-grained soils, such as that reported by Li et al (2012Li et al ( , 2019. The strength and stiffness of granular soils have been shown to be highly dependent on numerous factors related to soil properties (porosity [directly related to void ratio, density]), grain characteristics (particle size and shape), and test conditions (effective stress, strain rate).…”
Section: The Geomechanical Behavior Of Laboratory Synthesized Gas Hyd...mentioning
confidence: 99%
“…Experimental results have shown that hydrate saturation is positively related to the shear strength of HBSs. To increase the accuracy of the simulation results, the shear strength proposed by Song et al . was selected from a series of triaxial tests.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…89 Moreover, Li et al indicated that the burial depth was not directly relevant to the stress− strain behaviors of GHBS, but the particle size, aggregated morphology change, and the particle gradation had influences on the mechanical properties. 90 It is also noteworthy that scientists had attempted to using different clays to take the place of the hard-to-obtain shallow marine soil from the SCS. The comparison of mechanical experiment results between them indicated that clay such as kaolin and montmorillonite can be used as the alternates of the marine sediments while studying the mechanical properties of GHBS from the SCS.…”
Section: Advances On Natural Gas Hydratementioning
confidence: 99%
“…It was tested that hydrate cementing soil particles enhanced the failure strength of sediments, and it was responsible for the effect of cohesion and internal friction angle on the strength of GHBS . Moreover, Li et al indicated that the burial depth was not directly relevant to the stress–strain behaviors of GHBS, but the particle size, aggregated morphology change, and the particle gradation had influences on the mechanical properties . It is also noteworthy that scientists had attempted to using different clays to take the place of the hard-to-obtain shallow marine soil from the SCS.…”
Section: Advances On Natural Gas Hydrate Geophysical Property In the Scsmentioning
confidence: 99%